2013
DOI: 10.1007/s10534-013-9624-4
|View full text |Cite
|
Sign up to set email alerts
|

Production of LPS-induced inflammatory mediators in murine peritoneal macrophages: neocuproine as a broad inhibitor and ATP7A as a selective regulator

Abstract: Copper chelation regulates the production of inflammatory mediators in vivo during vascular inflammation and atherogenesis. Little is known about how the copper egress pump ATP7A regulates the production of these mediators. In this study, we isolated ATP7A deficient macrophages (MΦ) from the peritoneal cavity of blotchy mice and identified the lipopolysaccharide (LPS)-induced inflammatory mediators that were altered by ATP7A deficiency. These results were compared with the effect of neocuproine (a copper chela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 65 publications
0
9
0
Order By: Relevance
“…The nature of ATP7A angiogenic involvement is not exclusively associated with copper egress. Accordingly, a recent study in blotchy mice has demonstrated that macrophage ATP7A selectively regulates the release of some lipopolysaccharide-induced cytokines, including MCP-1 (monocyte chemoattractant protein 1), MCP-2 and VEGF-A, a potent angiogenic inducer [150]. A noticeable conclusion of that study, casting light on some copper-mediated angiogenic mechanisms, is that metal chelation and elevation trigger overlapping patterns of secretion of angiogenic mediators.…”
Section: Role Of Copper Transport Systems During Angiogenesismentioning
confidence: 99%
“…The nature of ATP7A angiogenic involvement is not exclusively associated with copper egress. Accordingly, a recent study in blotchy mice has demonstrated that macrophage ATP7A selectively regulates the release of some lipopolysaccharide-induced cytokines, including MCP-1 (monocyte chemoattractant protein 1), MCP-2 and VEGF-A, a potent angiogenic inducer [150]. A noticeable conclusion of that study, casting light on some copper-mediated angiogenic mechanisms, is that metal chelation and elevation trigger overlapping patterns of secretion of angiogenic mediators.…”
Section: Role Of Copper Transport Systems During Angiogenesismentioning
confidence: 99%
“…7,18,19,31 The overproduction of the inflammatory mediators contributes to the pathogenesis of several diseases such as sepsis, rheumatoid arthritis, atherosclerosis, pulmonary fibrosis, and chronic hepatitis. 32 Several nonsteroidal anti-inflammatory drugs were the currently available drugs to reduce the inflammation, but it possess a side effect and major problem.…”
Section: Resultsmentioning
confidence: 99%
“…However it is controversial whether these macrophages are activated or not since their physiological characteristics may be different from resident cells [ 15 ]. Macrophages elicited after intra-peritoneal injection of LPS show an infl ammatory/M1 phenotype [ 16 ] whereas injection of IL-4 after thioglycollate increases the amount of M2 macrophages that can be directly recovered from the peritoneal cavity [ 17 ].…”
Section: Notesmentioning
confidence: 99%